Efficacy and safety of ciprofol versus propofol for induction of general anaesthesia or sedation: A systematic review and meta-analysis of randomised controlled trials - Abdallah Saeed; Mariam Elewidi; Ahmad Nawlo; Amr Elzahaby; Asmaa Khaled; Abdalla Othman; Mohamed Abuelazm; Basel Abdelazeem (Indian Journal of Anaesthesia)
Background and Aims: Propofol has been used in medical practice as an anaesthetic drug for producing and sustaining general anaesthesia due to its advantages. However, it also has drawbacks, including injection-related discomfort. Recently, ciprofol has emerged as a promising anaesthetic drug that may overcome many drawbacks associated with propofol. In this systematic review and meta-analysis, we assess the efficacy and safety of ciprofol compared to propofol in different anaesthesia procedures. Methods: The study protocol was registered in the International Prospective Register of Systematic Reviews (ID: CRD42023458170). Central, PubMed, EMBASE, Scopus and WOS were searched for English literature until 26 February 2024. Meta-analysis was performed using RevMan. The risk of bias was assessed using the RoB 2.0 tool. Results were reported as risk ratios (RRs), mean differences (MDs) and 95% confidence intervals (CIs). Results: Nineteen randomised controlled trials were included in our analysis, with 2841 participants. There was no difference between ciprofol and propofol in the success rate of endoscopy (RR: 1.01, 95% CI: 0.99, 1.02; P = 0.44), while ciprofol showed a significant increase in the success rate of general anaesthesia/sedation (RR: 1.01, 95% CI: 1.00, 1.02; P = 0.04). Ciprofol showed significantly lower pain on injection (RR: 0.14, 95% CI: 0.09, 0.22; P < 0.001), lower adverse events (RR: 0.80, 95% CI: 0.69, 0.92; P = 0.002) and higher patient satisfaction (standardised mean difference (SMD): 0.36, 95% CI: 0.24, 0.48; P < 0.001). Conclusion: Ciprofol exhibited a comparable efficacy to propofol in inducing general anaesthesia and sedation with fewer adverse events, less pain on injection and higher patient satisfaction. These collective findings may suggest that ciprofol can be used as an alternative drug to ensure effective general anaesthesia/sedation induction in the future.